2023
DOI: 10.5751/es-14133-280224
|View full text |Cite
|
Sign up to set email alerts
|

Toward spatial fit in the governance of global commodity flows

Abstract: Global commodity flows between distally connected social-ecological systems pose important challenges to sustainability governance. These challenges are partly due to difficulties in designing and implementing governance institutions that fit or match the scale of the environmental and social problems generated in such telecoupled systems. We focus on the spatial dimension of governance fit in relation to global commodity flows and telecoupled systems. Specifically, we draw on examples from land use and global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Scales at which natural resources are governed often do not match with the scale of environmental and social dynamics [ 127 ]. In Oudomsin, individual fines were ineffective against collective deforestation decisions, and collective sanctions or incentives may have been more effective in preserving village forests.…”
Section: Discussionmentioning
confidence: 99%
“…Scales at which natural resources are governed often do not match with the scale of environmental and social dynamics [ 127 ]. In Oudomsin, individual fines were ineffective against collective deforestation decisions, and collective sanctions or incentives may have been more effective in preserving village forests.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, scholars have advocated for expanding such frameworks beyond the state domain to address global-scale environmental challenges [35]. Expanding upon van Koppen and Bush [35] and Coenen et al [36]'s prior work in adapting spatial fit to the context of globalized commodity flows, we assess both spatial fit and functional fit in the context of palm oil supply chains to account for both ecological and equity concerns arising from ZDC policy design and implementation in distant producing areas.…”
Section: Defining Spatial and Functional Fitmentioning
confidence: 99%
“…Following Moss [34], we define spatial fit as the alignment between the geographical scope of a governance arrangement and the ecological system it addresses. Previous research has explored the relevance of the spatial fit concept in the context of global commodity flows [33][34][35][36]. We present the first attempt to apply this concept to dataintensive analysis and additionally examine the functional fit of ZDCs, which we define as the alignment between a governance arrangement's policy design and the local socio-ecological contexts it addresses (see also [37]).…”
Section: Introductionmentioning
confidence: 99%
“…having their own institutional configuration, scope, and scale of action, and following their own operational procedures. Multiple actors play a role in the causal chain of environmental impacts, with no single governance institution having a response mandate that matches the scale of GVCs dynamics, which is a phenomenon described as institutional mis-match or mis-fit (Coenen et al, 2023). Following collective concerns calling for global action, multiple governance mechanisms have been proposed to tackle this problem.…”
Section: Addressing the Telecoupled Impacts Of Gvc And The Cocoa Valu...mentioning
confidence: 99%
“…Legally binding regulations, supporting bottom-up participation schemes, and setting up jurisdictional approaches that include multi-stakeholder coalitions are some of the potential options to help voluntary initiatives achieve net sustainability gains. However, research has shown that any single sustainability governance intervention is unlikely to match 143 Synthesis the scale of the environmental and social problems generated by telecoupled systems, such as the cocoa GVC(Coenen et al, 2023;Newig, 2018). Therefore, a combination of governance approaches is needed to address these scale mismatches.…”
mentioning
confidence: 99%